Association between Digital Addiction and Sleep Habits for Preschool Children - Ahmed Sabah Neamat, Adraa Hussein Shawq, Wasnaa Jomaa Mohammed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Excessive screen time has been shown to be a harmful habit that starts in the beginning of child life. However, little is known about the factors that influence children use of digital media. Increased digital time in young children has been associated to unfavorable health effects, such as an increase in BMI. Objective(s): The aim of this study is to detect the association between digital addiction and sleep habits for preschool children. Methodology: A descriptive (Cross-Sectional Design) study was conducted on preschooler’s parents by using the instrument of the study, the study was carried out through different governmental kindergartens at Al-Russafa and Al-Karkh Districts in Baghdad City to assess sleep habits regarding digital screen addiction for preschool children through period from November 1st, 2021, to March 7th 2022. The accessible population included the preschooler’s parents whom their children attended to Government kindergartens. Non-probability, convenient sample of (200) child and parents is selected; (100) participant from Al-Rusafa District Government Kindergartens and (100) participant from Al-Karkh District Government Kindergartens. Results: The results indicates that 62% of preschooler using digital screens at moderate level of addiction, and the mean score was moderate (30.03±4.039), and that 53% of preschool children show fair level of sleep style, and the mean score was fair (39.19±4.513). Conclusion: More than half of the study sample scored on moderate level on digital screen addiction. Half of study sample scored on fair level of sleep style. Recommendations: Increase parent’s awareness about the negative effect of digital screen up on children by social media and educational posters. More future studies about the effects of digital screen up on the different age groups of children.